Impact of Educational Intervention on Nurses’ Knowledge, Practice and Attitude Related Prevention Measures of COVID 19 - Gehan Abd Elfattah atia Elasrag; Nahed Elnabawy Elsabagh; Asmaa Foad Abdelmonem; Alaa Anwar Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The COVID-19 pandemic has not only caused highly significant challenges for health systems over the world, but also fueled a surge in misinformation. Nurses as the first member at health team must improve their performance about COVID-19 Research Aim: to assess impact of educational program on nurses’ knowledge, practice and attitude related prevention measures of COVID 19 Methodology: A Quasi-experimental research design was utilized from July 2020- November 2020 conducted at Shebin El Koum teaching Hospital and Menofia University Hospital for 50 nurses. A self-administered questionnaire containing four parts (characteristics, knowledge part, Attitude Rating Scale and nurses’ practice) Results: The present study showed mean age of studied nurses was 34.80±4.99 years and 52% of them providing care for COVID-19 patients. 70% of them had poor knowledge at pre intervention, while76% of them had good knowledge at post intervention and only 6% had poor knowledge. Mean score of studied nurses related total attitude at pre intervention was 13.70±3.45, while at post intervention was 25.18±3.66. Total practice, showed that 36% of nurses had competent practice while 90% of them had competent practice at post intervention with p value <0.01 Conclusions: To conclude, the present study reported that educational training program had positive effect on nurses’ knowledge, attitude and practice so hypothesis was accepted.